1993
DOI: 10.1093/ije/22.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Sudden Unexpected Death Syndrome among Thai Migrant Workers in Singapore

Abstract: A total of 235 cases of sudden unexpected death syndrome (SUDS) among apparently healthy male Thai migrant workers in Singapore were reported between 1982 and 1990. Most of the deaths occurred during sleep and 13% were not sleep-related. The median age at the time of death was 33 years and the median interval between arrival and death was 8 months. These deaths occurred singly and sporadically throughout the year. Post-mortem examination revealed few abnormal findings except for haemorrhagic congestion or oede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 0 publications
1
16
2
1
Order By: Relevance
“…Until now, many western and some Japanese investigators [20,[23][24][25][26] have demonstrated that sudden death occurred most frequently in the morning with or without a secondary peak in the afternoon or evening. However, some of them [25,26] also mentioned that the morning peak was diminished for younger people, and another investigator [27] reported that the peak of witnessed cases was observed during the night for young Thai workers. Coronary artery spasm, not uncommon among middle-aged Japanese people [28,29] , is usually induced late at night or early in the morning, and may play an important role in sudden death [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Until now, many western and some Japanese investigators [20,[23][24][25][26] have demonstrated that sudden death occurred most frequently in the morning with or without a secondary peak in the afternoon or evening. However, some of them [25,26] also mentioned that the morning peak was diminished for younger people, and another investigator [27] reported that the peak of witnessed cases was observed during the night for young Thai workers. Coronary artery spasm, not uncommon among middle-aged Japanese people [28,29] , is usually induced late at night or early in the morning, and may play an important role in sudden death [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Toxicological studies have not demonstrated poisons in the body fluids or organs. The concentration of alcohol in the body fluids was nil or negligible [1,5].…”
Section: Hypotheses Proposed To Explain Sundmentioning
confidence: 99%
“…In Singapore, the victims were usually employed in moderately heavy manual jobs such as labourers, construction workers, handymen or gardeners. Most of these deaths happen during the first year of residence in their adopted country [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive physical workload and heat stress have been identified as factors that could result in sudden unexplained death syndrome [5].…”
Section: Introductionmentioning
confidence: 99%